Analog circuit techniques : with digital interfacing - Wilmshurst, T. H. (Newnes, 2001)
This book uses an analytical approach, backed up with numerous experimental exercises and worked examples. It is designed to deliver the core content of a three year degree course in a single volume, which makes it an ideal core adoption text, and an essential reference text for a wide range of studentsA comprehensive analog electronics text for first degrees and conversion coursesDr Wilmshurst has drawn on his experience running an MSc conversion and other courses to produce this single volume text which covers all the analog electronics needed in a wide range of higher education programmes.